Pathological Lesions in Chicken Embryo Caused by Newly Virulent Isolate of Newcastle Disease Virus (LESI PATOLOGIS PADA EMBRIO AYAM YANG DISEBABKAN ISOLAT VIRUS PENYAKIT TETELO TERBARU YANG VIRULEN) - Wicaksana, I Gede Hendra Prasetya; Adi, Anak Agung Ayu Mirah; Kardena, I Made (Jurnal Veteriner; Vol 20 No 3 (2019), 2019)
Newcastle disease is a pathogenic viral disease in poultry which is infectious and can cause massive economic losses. The disease is still endemic in Indonesia. To understand the pathogenesis and the distribution pattern of the virus in the tissues, pathological observation was evaluated using newly virulent isolate Newcastle disease virus (NDV) that was inoculated in embryonated chicken eggs. As many as seven embryonic chicken eggs aged 11 days and specific antibody negative against Newcastle disease, divided into two categories: inoculated with phosphate buffer saline and inoculated with isolates. Then the allantois fluid was tested using hemagglutination assay and hemagglutination inhibition tests to prove the infection serologically. The hearts, lungs, livers and small intestines of the inoculated products were collected and followed with the process of histopathological preparation using Hematoxylin and Eosin (HE) stain. The pathological analysis showed that all organs had necrosis, hemorrhages, inflammation, and congestion. Congestion and hemorrhages in the hearts only occurred at 60% of the samples. However, necrosis, hemorrhages, and inflammation that were observed in liver occurred at 60%, 40% and 60% of the samples, respectively. Furthermore, the hearts were edema, thinner in the heart muscle fibers; while in the lungs, proliferation of pneumocyte type II was founded. Our finding provided valuable insight into the pathology of a virulent isolate of NDV which is dominated by blood circulation disorders with necrosis and inflammation in the chicken’s embryos and have important implication for the future studies.